EU Emission Allowances and the Stock Market: Evidence from the Electricity Industry - Ulrich Oberndorfer (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
This paper constitutes – to our best knowledge – the first econometric analysis on stock market effects of the EU Emission Trading Scheme (EU ETS). Our results suggest that EU Emission Allowance (EUA) price developments matter to the stock performance of electricity firms: EUA price changes and stock returns of the most important European electricity corporations are shown to be positively related. This effect does not work asymmetrically, so that stock markets do not seem to react differently to EUA appreciations in comparison to depreciations. The carbon market effect is shown to be both time- and countryspecific: It is particularly strong for the period of EUA market shock in early 2006, and differs with respect to the countries where the electricity corporations analysed are headquartered. Stock market reactions to EUA volatility could not be shown. – – Dieses Papier untersucht die Aktienmarkteffekte von Preisentwicklungen auf dem Markt für Emissionszertifikate im Rahmen des Europäischen Emissionshandelssystems (EU ETS). Die Analyse fokussiert dabei auf die Aktienmarktperformance des europäischen Elektrizitätssektors, der gemessen an CO2-Emissionen größten Branche im EU ETS. Nach unseren Ergebnissen spielt der Zertifikatmarkt eine wichtige Rolle für die Aktienentwicklungen der analysierten Elektrizitätsfirmen. Ein Anstieg des Zertifikatpreises sorgt für Kursgewinne bei den Aktien der Elektrizitätsfirmen aus fast allen europäischen Ländern. Hingegen scheint die Volatilität der Emissionsrechte entgegen anderslautender Erwartungen nicht auf die Aktienkursentwicklung der untersuchten Unternehmen zu wirken.
Keywords: Q43; Q48; C13; G12; 330; EU ETS; electricity stocks; asset pricing; Emissionsrechte; Kohlendioxid; Börsenkurs; Elektrizitätswirtschaft; EU-Staaten